PULSED ELECTROMAGNETIC FIELD THERAPY USING SENTIENT ELEMENT FOR MANAGEMENT AND CHONDROPROTECTIVE EFFECTS ON HUMAN ARTICULAR CARTILAGE IN EARLY-STAGE OSTEOARTHRITIS: AN OBSERVATIONAL AND OPEN-LABEL PILOT STUDY - ABHIDHYA REDDY,; SHEETAL MEENA,; KARKALA SRIKANTH REDDY,; VAIBHAV KUMAR GUPTA,; VAISHNAVI AMBATIPUDI,; SHAHEEN FATIMA,; SHAZIA THAZEEN,; SYED IRFAN DAWER,; rao, PENAKALAPATI SAILAJA RAO (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The present study aimed to evaluate the role of pulsed electromagnetic field therapy (PEMF) in managing pain, stiffness, and chondroprotective effects on human articular cartilage in early-stage osteoarthritis (OA). Methods: In the present study the effectiveness of PEMF in Osteoarthritis (OA) patients was conducted using an open-label pilot study and observational data. Ten people with OA in their left and right knees were included. The standard error of the mean, or Mean±Standard deviation, was used to express all data. An IBM Statistical package for the social sciences (SPSS) software (version 11.0) was used to analyse the significance of evaluated parameters. T-test was used to examine the information gathered from clinical interventions. Results: The result of the study discussed the before and after effect of the PEMF therapy in OA patients with knee pain in both legs. The knee pain and physical function were decreased in the patients for both the legs after the therapy. Using statistical tests, pain score, stiffness score, and cartilage health were analyzed in the patients to record a significant effect of PEMF therapy. Conclusion: All the examination reports exerted positive effects of the implementation of the therapy in pain management and enhancing mobility of the knee joints.